2sinx*cosx-sinx-cosx-1=0

Simple and best practice solution for 2sinx*cosx-sinx-cosx-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2sinx*cosx-sinx-cosx-1=0 equation:


Simplifying
2sinx * cosx + -1sinx + -1cosx + -1 = 0
Multiply insx * cosx
2cinos2x2 + -1sinx + -1cosx + -1 = 0
Reorder the terms:
-1 + 2cinos2x2 + -1cosx + -1insx = 0
Solving
-1 + 2cinos2x2 + -1cosx + -1insx = 0
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 2cinos2x2 + -1cosx + 1 + -1insx = 0 + 1
Reorder the terms:
-1 + 1 + 2cinos2x2 + -1cosx + -1insx = 0 + 1
Combine like terms: -1 + 1 = 0
0 + 2cinos2x2 + -1cosx + -1insx = 0 + 1
2cinos2x2 + -1cosx + -1insx = 0 + 1
Combine like terms: 0 + 1 = 1
2cinos2x2 + -1cosx + -1insx = 1
Add 'insx' to each side of the equation.
2cinos2x2 + -1cosx + -1insx + insx = 1 + insx
Combine like terms: -1insx + insx = 0
2cinos2x2 + -1cosx + 0 = 1 + insx
2cinos2x2 + -1cosx = 1 + insx
Reorder the terms:
-1 + 2cinos2x2 + -1cosx + -1insx = 1 + insx + -1 + -1insx
Reorder the terms:
-1 + 2cinos2x2 + -1cosx + -1insx = 1 + -1 + insx + -1insx
Combine like terms: 1 + -1 = 0
-1 + 2cinos2x2 + -1cosx + -1insx = 0 + insx + -1insx
-1 + 2cinos2x2 + -1cosx + -1insx = insx + -1insx
Combine like terms: insx + -1insx = 0
-1 + 2cinos2x2 + -1cosx + -1insx = 0
The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| 7x+6x/3x+4=10 | | sinx(2cosx-1)-cosx-1=0 | | -2x+5x-7=5 | | 2x+38=142 | | 15y-1=5.5y+2 | | 3x+7-2x+9=12 | | x^2-1b=0 | | 2x+38=142findx | | (5xa)-(4xy)=11 | | 79-71=33y-41y | | 13+3x=76 | | 6x+5=4x+21 | | 7x+3x/5x+9=12 | | .7(1.5+y)=3.5y-1.47 | | .88x=15 | | z=5x+7 | | Lin(5x)=3 | | 10n+60=60+10n | | 2x-50=150 | | 6p+2= | | -4(y+6)+y= | | 3.5x-9+x-11=4x+13 | | f(x)=9-6x | | 3x22/3x1/3 | | 10z+7=6 | | x-0.30x=120000 | | 21/2x11/2x4 | | 12/6-2/3 | | 7x-0.375=6x-.625 | | -9(3x-v-5)= | | y+9*2=34 | | 5-7=15 | | Y+5x+6=0 | | 3x*2x=150 | | 2xy(4xy)(3x)= | | Y-7x=-2 | | 5[y+2]-15=0 | | 2x+3.5-11.5= | | y=15+5*5 | | w(5w3)-2/w-4 | | K+k+k+k+K+k=-96 | | x+3=10 | | 53.17-1.66= | | 2y^2+5sqrt(2)+6=0 | | 5y+5y+5y+5y=80 | | 3xy+x=2y-1 | | 10y-4y=18 | | 3n+3n+3n=81 | | C+c+c+c+c+c+c=91 | | (3x+10)+(4x-20)=180 | | X+x+x+x+x+x=75 | | 9a-a=32 | | 3[y+2]-18=0 | | X-3(3/4)=1/8 | | 2x+3(x-2)=6x+8 | | 2y-18=5x | | (2/3)^1/2 | | -14x+6=6 | | -2.5x-20=9x+37.5 | | 19w-13w+6=54 | | 38-3n=2+n | | 8x^(3/5)=27 | | 15z-18=27 | | (r-2)(5r-2)=0 | | 14x+11x=75 |


Related pages


220-33abd abcrewrite without parentheses and simplifyfactor 4x 2 16x 16lcm of 613x 5x 3what is the prime factorization of 164tham solution72 in roman numeralsgreatest common factor of 48 and 54esxy1km 1000m4x 2 6xfactor tree of 843pi 4prime factorization for 128the lcm of 2 and 48y y8find the prime factorization of 40solve this quadratic equation x2 5x 3 0derivative of x tanxprime factorization of 684180-115prime factorization 252343 cubed9y-1 y-25loga logbwhat is 5.25 as a fractiongraph x 2y 6maths solution solverprime factorization of 21263-14gcf of 120what is cos 3xtwo step equation calculator with fractions1991 roman numeral1.1811 to fraction2lw3ixmath algebra calculator with steps4x 3y 6derivative of 3 ln xprime factors of 4411962 in roman numeralshow to factor with gcfautonline.aut.ac.nzwhat is the prime factorization of 248prime factorization for 65how to solve 2x-5y 10prime factorization of 4202izgraph y 2x-6onslow powerschoolmultiplying and dividing fractions calculatorcos2 pi4x 3y 6derivative of sin-1xderivative xe x 2write the prime factorization of 32700-20sin xy derivative4x 2 9y 2 36prime factors of 490if 8x 5x 2x 4x 114 the 5x 3square root of 1296the prime factorization of 114220-155esay solutionsfactoring x 3-27x 2 bx c 01.32 inches to fractionaforp